The Role of Critical Consciousness and Parental Acceptance in LGBTQ+ Youth Mental Health - Teresa Vazquez; Rodrigo Costa; Roberto L. Abreu (Social Sciences)
Research shows that parental acceptance can serve as a protective factor against negative mental health outcomes among LGBTQ+ youth. Although a few studies have examined the role of critical consciousness in mental health outcomes among LGBTQ+ youth, findings are often inconsistent and do not provide a clear picture. Thus, the present study aims to fill this knowledge gap. Using a sample of LGBTQ+ youth aged 18–25 (N = 460), the present study explores the relationship between critical consciousness, mental health outcomes (depression, anxiety, and flourishing), and the buffering role of parental support using bivariate correlations and moderated regression analyses. Findings show that (1) higher critical consciousness was associated with lower flourishing, (2) higher parental acceptance was associated with lower depressive and anxiety symptoms and greater flourishing, and (3) parental acceptance did not moderate the relationships between critical consciousness and mental health outcomes. The results of this study illustrate that while parental acceptance is a positive factor for mental health outcomes among LGBTQ+ youth, different dimensions of critical consciousness may have varying effects on mental health well-being for this population. Implications for research, clinical practice, and advocacy, such as examining peer support and community healing, are discussed in relation to these findings.